THE IMPLEMENTATION OF DIGITALIZATION OF STANDARD ACCOUNTING SYSTEMS IN THE AGRICULTURAL INDUSTRY - Verma, Naveen; Rajput, Sheetal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The agriculture sector, traditionally reliant on manual processes and informal accounting, is experiencing a transformation with the digitalization of standard accounting systems. This paper explores the impact, challenges, and opportunities of integrating digital accounting technologies in agricultural enterprises, with a focus on smallholder farms, cooperatives, and agribusinesses. It highlights how digital accounting can enhance transparency, access to finance, compliance, and overall efficiency. The digitalization of standard accounting systems in the agriculture sector is revolutionizing the way farmers and agribusinesses manage their financial operations. Traditionally, accounting in agriculture has relied on informal, manual methods, leading to inefficiencies, lack of transparency, and limited access to credit and government support. With the growing availability of digital tools—such as cloud-based accounting software, mobile applications, and integrated farm management systems—agricultural enterprises can now record, track, and analyze financial data in real time. This shift enables better financial planning, compliance with tax regulations, improved access to financing, and overall operational efficiency. However, the adoption of digital accounting in agriculture is not without challenges, including limited digital literacy, poor rural infrastructure, high costs, and resistance to change. This paper examines the current trends, benefits, barriers, and policy implications of accounting digitalization in the agriculture sector, emphasizing the need for coordinated efforts by governments, financial institutions, and technology providers to ensure inclusive and sustainable adoption.